AR-42: A Pan-HDAC Inhibitor with Antitumor and Antiangiogenic Activities in Esophageal Squamous Cell Carcinoma - Zhu Y; Yuan T; Zhang Y; Shi J; Bai L; Duan X; Tong R; Zhong L (Dove Medical Press, 2019)
Yuxuan Zhu,* Ting Yuan,* Yuan Zhang, Jianyou Shi, Lan Bai, Xingmei Duan, Rongsheng Tong, Lei Zhong Personalized Drug Therapy Key Laboratory of Sichuan Province, Department of Pharmacy, Sichuan Provincial People’s Hospital, University of Electronic Science and Technology of China, Chengdu, Sichuan 610072, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lei Zhong; Rongsheng TongPersonalized Drug Therapy Key Laboratory of Sichuan Province, Department of Pharmacy, Sichuan Provincial People’s Hospital, University of Electronic Science and Technology of China, No. 32 West Second Section First Ring Road, Chengdu, Sichuan 610072, People’s Republic of ChinaTel +86 13458580284; +86 28-87393405Email zhl7235301@163.com; 1505855365@qq.comPurpose: Esophageal squamous cell carcinoma (ESCC) is a refractory malignancy with high morbidity and mortality. Thus, there is an urgent need to find effective targets and agents for ESCC treatment. The purpose of this study was to assess the anti-ESCC effects of a pan-histone deacetylase (HDAC) inhibitor AR-42 and its mechanisms of action.Methods: Immunohistochemical staining was performed to detect HDAC1 expression in ESCC and adjacent tissue samples. MTT assay, Edu cell proliferation test, flow cytometry, and subcutaneous xenograft were used to assess the anti-ESCC effects of AR-42; furthermore, the antiangiogenic activity of AR-42 was evaluated using endothelial cell migration, invasion, and tube formation assays as well as zebrafish angiogenesis assay. Western blot analysis was performed to explore the underlying mechanism of the anti-ESCC activity of AR-42.Results: HDAC1-positive expression was much higher in ESCC cells than in paracancerous tissues, and the elevated HDAC1 expression was a strong indicator of lymph node metastasis and a more advanced TNM stage of ESCC. Moreover, AR-42 potently suppressed ESCC cell growth through cellular proliferation inhibition and apoptosis induction. Moreover, AR-42 displayed a moderate antiangiogenic activity, and it could significantly inhibit the migration, invasion and tubulogenesis of human umbilical vein endothelial cells as well as intersegmental vessel formation in zebrafish at micromolar concentrations. More importantly, the inhibitory activity of AR-42 on ESCC cells and angiogenesis could also be observed in the TE-1 xenograft model. Further studies showed that AR-42 exerts its anti-ESCC effects mainly by upregulating the expression of p21 and blocking the transduction of multiple signaling cascades related to tumor growth, especially Stat3-mediated signaling.Conclusion: Overall, AR-42 has significant potency for inhibiting ESCC cell growth and shows moderate effect in suppressing angiogenesis, displaying strong anti-ESCC effects in vitro and in vivo. Thus, AR-42 deserves further evaluation as a potential candidate for ESCC therapy.Keywords: esophageal squamous cell cancer, AR-42, histone deacetylase, angiogenesis